2015
DOI: 10.1097/ccm.0000000000001353
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Impact of Unknown Diabetes in the ICU

Abstract: Patients with unknown diabetes represent a significant percentage of ICU admissions. Measurement of hemoglobin A1c at admission can prospectively identify a population that are not known to have diabetes but have significant challenges in glycemic control in the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 43 publications
1
43
0
3
Order By: Relevance
“…Because inpatient insulin use (5) and discharge orders (6) can be more effective if based on an A1C level on admission (7), perform an A1C test on all patients with diabetes or hyperglycemia admitted to the hospital if the test has not been performed in the prior 3 months. In addition, diabetes self-management knowledge and behaviors should be assessed on admission and diabetes self-management education (DSME) should be provided, if appropriate.…”
Section: Considerations On Admissionmentioning
confidence: 99%
“…Because inpatient insulin use (5) and discharge orders (6) can be more effective if based on an A1C level on admission (7), perform an A1C test on all patients with diabetes or hyperglycemia admitted to the hospital if the test has not been performed in the prior 3 months. In addition, diabetes self-management knowledge and behaviors should be assessed on admission and diabetes self-management education (DSME) should be provided, if appropriate.…”
Section: Considerations On Admissionmentioning
confidence: 99%
“…Previous epidemiological studies report the prevalence of unknown diabetes to be between 5 and 10% of patients admitted to ICU [2, 28]. To limit the likelihood of unknown diabetes being a major confounder prevalent diabetes was identified by a thorough process including verifying across two separate databases (using ICD-10 codes and NDSS registration) and excluding patients with a blood glucose > 20 mmol/L (360 mg/dL), or who registered with the NDSS within 30 days of hospital discharge, were excluded [16].…”
Section: Discussionmentioning
confidence: 99%
“…44 Patients with an unknown diagnosis of diabetes at the time of critical illness (HbA1c > 6.5%, without history of diabetes) have been identified as not only having significantly worse dysglycemia but also an increased mortality risk (13.8 vs. 11.4%; p ¼ 0.01) compared with those without diabetes. 69 It is not only the history of diabetes (diagnosed or undiagnosed) but also the metabolic control prior to critical illness that seems to affect outcomes in the ICU. In a critically ill cohort, Plummer and colleagues 6 showed that in patients with DM and very good (HbA1c < 6%) and adequate prior metabolic control (HbA1c between 6 and 7%), an increase in peak BG in the first 48 hours of critical illness was associated with increased mortality, whereas patients with poor baseline control tolerated higher peak BG better.…”
Section: Role Of Pre-existing Diabetes Mellitusmentioning
confidence: 99%